Scientific and Quantitative Literacy and Its Influence on Academic Achievement in Physical Science - Estillena, Rea Joy S.; Linaugo, Joji D. (Philippine Social Science Journal, 2025)
Grounded in Constructivist and Progressive Education theories, this descriptive-correlational study assessed the relationships between scientific literacy, quantitative literacy, and Physical Science academic achievement among 231 Grade 12 students in the Negros Island Region during the 2024–2025 academic year. Results indicated that while students demonstrated "developing" literacy skills and "approaching proficiency" in academic achievement, significant positive correlations exist between these foundational literacies and science performance. These findings highlight the necessity of integrating literacy-focused teaching strategies and justify the development of supplementary activity sheets to enhance student outcomes. Consequently, the study recommends future research into the scalability and longitudinal impact of such interventions to support inclusive science education.